Temperature-dependent sex determination in the Nile crocodile, Crocodylus niloticus, in the Okavango River, Botswana, and the effect of global climate change - Maciejewski, Kristine (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2006.